32-Gb/s OOK and 64-Gb/s PAM-4 Modulation Using a Single-Drive Silicon Mach–Zehnder Modulator with 2 V Drive Voltage - Gangqiang Zhou; Linjie Zhou; Yuyao Guo; Shuhuang Chen; Liangjun Lu; Lei Liu; Jianping Chen (IEEE Photonics Journal)
We demonstrate a high-efficiency silicon Mach-Zehnder modulator with U-shaped PN junctions. The depletion region of the U-shaped PN junction has a large overlap with the waveguide optical mode, leading to a low drive voltage. The calculated modulation efficiency is 0.33 V·cm at 0 V bias and 0.55 V·cm at −2 V bias. On-off keying (OOK) modulation and four-level pulse amplitude modulation (PAM-4) are achieved at 32 Gb/s and 64 Gb/s data rates under 2 V drive voltage, respectively. The bit error rate for the PAM-4 modulation is below the hard-decision forward error correction threshold of 3.8 × 10−3.